Biomechanical Evaluation of Clival Screw Fixation for Occipitocervical Instablity: A Finite Element Analysis - Weipeng Lin; Jianying Zheng; Meichao Zhang; Panjie Xu; Hang Xiao; Wei Ji (Orthopaedic Surgery)
ABSTRACT Objective The clivus is trapezoidal in shape with uneven bone structure, the optimal number and position of screws for clival fixation are not clear. Therefore, this study aims to explore the optimization clival screw fixation method for occipitocervical instability using finite element analysis. Methods Seven finite element models were developed to evaluate biomechanical properties of clival screw fixation for treating occipitocervical stability, including (i) one clival screw fixation A1 and A2 models; (ii) two clival screws fixation B1 and B2 models; (iii) three clival screws fixation C1 and C2 models; (iv) four clival screws fixation D1 model. Loads of 1.5 Nm were applied to the model fRoM different directions to induce flexion, extension, lateral bending, and axial rotation movements. Results The regular triangle C1 type three clival screws fixation exhibited great stability, with RoM of 4.20° in flexion, 5.80° in extension, 0.85° in lateral bending, and 1.60° in axial rotation. The peak stress on the internal fixation devices were relatively low, with maximum screw stress of 194 MPa in flexion, 276 MPa in extension, 180 MPa in lateral bending, and 213 MPa in axial rotation; the maximum plate stress were 126, 554, 426, and 378 MPa, respectively. The areas with higher stress were mainly concentrated at the robust neck section of the plate. Conclusion The triangular configuration of three clival screws fixation represented the optimized anterior occipitocervical fixation method through the clivus, offering superior biomechanical stability, lower stress on the devices and dispersed stress distribution in the occipitocervical region.